The dialectics of graffiti studies: a personal record of documenting and publishing on graffiti since 1988 - Jacobson, Malcolm (SAUC - Street Art and Urban Creativity (repository), 2015)
There is an abundance of books, magazines, films and internet-forums dedicated to graffiti. How this documentation has influenced and been a part of the graffiti subculture has not been studied much. Drawing on personal experiences, as a documentarian and publisher of graffiti media over 27 years, Malcolm Jacobson recollects how the positions of participant and observer incessantly have twisted around each other. This has been mediated through development in media technology as well as by the coming of age of graffiti and its practitioners.